1996
DOI: 10.1159/000113193
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Sensory Guidance of Mauthner-Mediated Escape Responses in Goldfish (<i>Carassius auratus</i>) and Cichlids (<i>Haplochromis burtoni</i>)

Abstract: Acoustically-evoked escape behaviors were compared between goldfish (Carassius auratus), a hearing specialist, and the cichlid Haplochromis burtoni, a hearing nonspecialist. Fish were startled with compressive and rarefying, stimuli presented alone or together, and with compressive pulses preceded by a visual cue or after exposure to cobalt, an inhibitor of lateral line-innervated neuromast hair cells. These acoustic startle stimuli can evoke Mauthner neuron firing and are similar to but weaker than those prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 0 publications
1
49
2
Order By: Relevance
“…The adjustment in activation threshold is consistent with feedforward inhibition of the Mauthner-cell circuitry underlying escape responses in goldfish (for review see Faber et al, 1989) that can be potentiated by sound stimuli (Oda et al, 1998). Canfield and Rose (1996) reported that largemouth bass (Micropterus salmoides) feeding on guppies produce ~170·dB (re 1·µPa, ~200·Hz), and in the same paper used ~150·dB (re 1·µPa, ~500·Hz) to elicit escape responses from goldfish. From our measurements, both adult and larval zebrafish would respond to the bass strike and the ~150·dB (re 1·µPa, ~500·Hz) used to elicit responses from goldfish.…”
Section: The Response Was Probably Mediated By the Sacculussupporting
confidence: 55%
“…The adjustment in activation threshold is consistent with feedforward inhibition of the Mauthner-cell circuitry underlying escape responses in goldfish (for review see Faber et al, 1989) that can be potentiated by sound stimuli (Oda et al, 1998). Canfield and Rose (1996) reported that largemouth bass (Micropterus salmoides) feeding on guppies produce ~170·dB (re 1·µPa, ~200·Hz), and in the same paper used ~150·dB (re 1·µPa, ~500·Hz) to elicit escape responses from goldfish. From our measurements, both adult and larval zebrafish would respond to the bass strike and the ~150·dB (re 1·µPa, ~500·Hz) used to elicit responses from goldfish.…”
Section: The Response Was Probably Mediated By the Sacculussupporting
confidence: 55%
“…Hence, receiving a weak ipsilateral stimulation (WS) prior to the startling stimulus did not increase the chances of responding away from the stimulus. In other fish species (goldfish Carassius auratus and cichlids Haplochromis burtoni) a directional visual stimulus displayed 10-100 ms prior to an acoustic non-directional startling stimulus was shown to affect escape direction, presumably by driving one of the Mauthner cells closer to firing threshold (Canfield, 2003;Canfield and Rose, 1996). In our experiment, the interval between WS and SS was relatively long (30 s), which may allow the Mauthner cells enough time to return to their normal firing threshold.…”
Section: Responses To Stimulation In the Horizontal Planementioning
confidence: 60%
“…Ablation of the lateral line increases the response latency of the 'acoustic' escape response in goldfish and alters the directionality of this response when tested with an underwater sound source , presumably due to electrical synapses with the Mauthner cells forming the motor aspects of the escape response . Interestingly, when goldfish startle responses are triggered with an airborne sound source, ablation of lateral line inputs improves escape responses (Canfield and Rose, 1996), suggesting that the relationship between particle motion and pressure waves in the stimulus can affect the relative role of the ear and lateral line. It is likely that in nature fish use inputs from both auditory and lateral line systems either simultaneously or in series (Braun and Coombs, 2000;Webb et al, 2008) to ascertain the true nature of 'sound' stimuli and make appropriate behavioural decisions.…”
Section: Discussionmentioning
confidence: 99%